2021
DOI: 10.1016/j.pediatrneurol.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement for the Management and Treatment of Sturge-Weber Syndrome: Neurology, Neuroimaging, and Ophthalmology Recommendations

Abstract: Background: Sturge-Weber syndrome (SWS) is a sporadic, neurocutaneous syndrome involving the skin, brain, and eyes. Because of the variability of the clinical manifestations and the lack of prospective studies, consensus recommendations for management and treatment of SWS have not been published. Objective: This article consolidates the current literature with expert opinion to make recommendations to guide the neuroimaging evaluation and the management of the neurological and ophthalmologic features of SWS. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
(59 reference statements)
0
24
0
1
Order By: Relevance
“…The associated risk of leptomeningeal or ocular involvement depends on the extent and location of the CM but it ranges from 7% to 28%. 26 Historically, it was thought that the distribution of facial PWB followed the distribution of the sensory innervation branches of the trigeminal nerve (ophthalmologic [V1], maxillary [V2], and mandibular [V3]) and that children with involvement of the first branch (V1) were at highest risk of SWS. [27][28][29] More recently, it has been demonstrated that the area of highest risk is the forehead, the area demarcated laterally and inferiorly by the outer margins of the canthus of the eye (including the upper eyelid) to the top of the ears.…”
Section: Dermatological Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated risk of leptomeningeal or ocular involvement depends on the extent and location of the CM but it ranges from 7% to 28%. 26 Historically, it was thought that the distribution of facial PWB followed the distribution of the sensory innervation branches of the trigeminal nerve (ophthalmologic [V1], maxillary [V2], and mandibular [V3]) and that children with involvement of the first branch (V1) were at highest risk of SWS. [27][28][29] More recently, it has been demonstrated that the area of highest risk is the forehead, the area demarcated laterally and inferiorly by the outer margins of the canthus of the eye (including the upper eyelid) to the top of the ears.…”
Section: Dermatological Manifestationsmentioning
confidence: 99%
“…PWB is commonly lateralized to one side of the face, but on rare occasions PWB can present at the medial forehead location. 26,65 Differentiation in these cases may be impossible from a clinical point of view and close follow-up or even brain imaging may be considered.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…Dessa forma, se considera de maior risco a MVP que afeta a pele derivada embriologicamente da proeminência frontonasal, pelo compartilhamento de células progenitoras cerebrais. São elas as regiões frontal, hemifacial e mediana (Sabeti et al, 2021;, além de regiões independentes como pálpebra superior, nariz, linha média superior e linha temporal . Também se nota que o tamanho da MVP e o envolvimento bilateral estão relacionados a maior risco e maior severidade do quadro clínico (Dymerska et al, 2017;Kaseka et al, 2016).…”
Section: Fatores De Risco E Indicações De Rastreamentounclassified
“…The teams of experts who comprise multidisciplinary clinics are up to date on current guidelines and ever-evolv-ing protocols of various syndromes. [43][44][45][46][47] Multidisciplinary meetings also occur in which providers meet to discuss, refine, and create protocols. 48,49 The multidisciplinary nature of clinics is especially useful in cases of dual diagnoses in which management must be further individualized.…”
Section: Guidelines and Protocolsmentioning
confidence: 99%